2023
DOI: 10.1177/10556656221148903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anxiety in Turkish Parents of Newborns with Cleft Palate with or Without Cleft Lip

Abstract: Objective (1) To compare anxiety between parents of newborns with cleft lip and palate (CLP), isolated cleft palate (CP), and healthy newborns and (2) to evaluate anxiety between parental dyads within these groups. Design A cross-sectional study. Setting University Hospital. Participants Surveys were completed by 20 mothers and 20 fathers of newborns with CLP, 21 mothers and 21 fathers of newborns with CP, and 23 mothers and 23 fathers of healthy newborns (controls). Main Outcome Measure The State-Trait Anxiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Parents of children with CL/P experience obvious depression and anxiety. It is consistent with the findings of previous studies reporting that parents of newborns with CL/P had significantly higher levels of anxiety compared to control parents [ 20 ]. The study findings are consistent with the current literature, as depression or depressed mood in parents of children with CL/P is a common phenomenon [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Parents of children with CL/P experience obvious depression and anxiety. It is consistent with the findings of previous studies reporting that parents of newborns with CL/P had significantly higher levels of anxiety compared to control parents [ 20 ]. The study findings are consistent with the current literature, as depression or depressed mood in parents of children with CL/P is a common phenomenon [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, previous studies [ 14 , 18 ] suggested that mothers of children with CL/P experienced severe stigma or discrimination while ignoring the possibility that fathers also experienced high levels of discrimination. Two other studies [ 19 , 20 ] pointed out that the main sources of stress among fathers were the treatment process, feeding, and social stigma. Therefore, in the care process of children with CL/P, we should not only focus on the mother’s psychological state but also consider the psychological state of the father.…”
Section: Discussionmentioning
confidence: 99%